2020
DOI: 10.1002/fam.2847
|View full text |Cite
|
Sign up to set email alerts
|

Studying smoldering to flaming transition in polyurethane furnituresubassemblies: Effects of fabrics, flame retardants, and material type

Abstract: The transition from smoldering to flaming was studied on fabric, batting, and foam assemblies via an electric spot ignition source of similar intensity to a cigarette. The materials studied included four different fabrics (cotton, polyester, cotton/polyester blend, flame retardant cotton/polyester blend), two types of batting (cotton, polyester), and three types of polyurethane foam (nonflame retardant, flame retardant by FMVSS 302 testing, flame retardant by BS5852 testing). The results from testing found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Transition from smoldering to flaming combustion has been studied extensively in recent years for, e.g., polyurethane foams [17,18], cotton [19], pine needles and wood powder [20], peat [21], and coal waste dumps [22], and since smoldering results in many deaths worldwide, much work has addressed preventing materials for initiating smoldering combustion, e.g., [23]. When it comes to the combination of glass fibers and polymers, several fire-related studies have focused on flaming combustion of glass fiber-reinforced epoxy resins, e.g., [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition from smoldering to flaming combustion has been studied extensively in recent years for, e.g., polyurethane foams [17,18], cotton [19], pine needles and wood powder [20], peat [21], and coal waste dumps [22], and since smoldering results in many deaths worldwide, much work has addressed preventing materials for initiating smoldering combustion, e.g., [23]. When it comes to the combination of glass fibers and polymers, several fire-related studies have focused on flaming combustion of glass fiber-reinforced epoxy resins, e.g., [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…For the transition to flaming combustion observed in the full-scale filter tests in the present study, it was not possible to determine the transition mechanisms. Several studies [17][18][19][20] consider the inclination and porosity of tested materials to be important for transition from smoldering to flaming combustion. In the present study, the filter cassettes allowed for inclined and vertical surfaces between individual filter bags where the suddenly fast-developing smoke plumes could be ignited.…”
Section: Discussionmentioning
confidence: 99%
“…Morgan et al studied the transition from smoldering to flaming using an electric spot ignition source (like a cigarette) on different fabrics, batting, and foams [ 176 ]. Results showed that materials prone to smoldering could lead to ignition, but materials that melted away from the ignition source did not transition to ignition.…”
Section: Fire Researchmentioning
confidence: 99%
“…The materials studied included different fabrics (cotton, polyester, cotton/polyester blend, flame retardant cotton/polyester blend), batting (cotton, polyester), and polyurethane foam (non-flame retardant and flame retardant by two different testings). The evolved gas analysis allowed us to compare the different behaviors [ 98 ].…”
Section: Applications To Flame Retardantsmentioning
confidence: 99%